A Detailed Review on Dihydropyrimidine Dehydrogenase Enzyme Deficiency-Autosomal Recessive Condition - Nirojini, P. Sharmila; Fathumuthu, A. Asma (Indian Journal of Pharmacy Practice)
Dihydropyrimidine dehydrogenase deficiency (DPD) is an autosomal recessive condition. The DPD enzyme is in charge of the 5-fluorouracil drug’s metabolism. Patients having DPD deficiency, when get administered with 5-fluorouracil drug, leads to drug toxicity due to increased concentration of drug in the body. Determining the DPYD (gene encoding DPD) genotyping and DPYD phenotyping will provide the best strategy to know the DPD deficiency in patients. Tegafur and Capecitabine are available prodrugs for the 5-fluorouracil medication. Genomic techniques appear to be a superior indirect evaluation for screening DPD deficiency in the clinical environment. Other than this there are several diagnostic tests such as Uracil oral loading dose, Uracil Breath test, Rapid UPLC-UV (Ultra performance liquid chromatography-Ultravoilet) method, and DPD activity in mononuclear cells from the peripheral circulation. An antidote Uridine Triacetate is available for treating the toxicity produced by 5-FU (5-Fluorouracil) in DPD deficient patient. Hence, this review explains briefly about the DPD enzyme, its deficiency, its diagnosis, and how to manage the DPD deficient patient undergoing chemotherapy.
Keywords: DPD; 5-Fluorouracil; Capecitabine; Tegafur; Uracil Breath test; Uridine triacetate